2010
DOI: 10.3813/aaa.918287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of loudness models for time-varying sounds

Abstract: SummaryThe loudness of as ound depends, among other parameters, on its temporal shape. Different loudness models were proposed to account for temporal aspects in loudness perception. To investigate different dynamic concepts for modeling loudness, predictions were made with the twocurrent loudness models of Glasbergand Moore [J. Acoust. Soc. Am. 50,331-341 (2002)] and Chalupper and Fastl [Acta Acustica united with Acustica 88,378-386 (2002)] for aset of time-varying sounds. The predicted effects of duration, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
(95 reference statements)
1
24
2
2
Order By: Relevance
“…In these models, the time constants employed at the first integration stage (i.e., to compute the STL) were based only on data from psychophysical experiments on temporal masking and temporal integration of loudness (Glasberg & Moore, 2002). Although some studies showed that these constants surprisingly lead to fairly accurate predictions of loudness asymmetries between short duration rising and falling stimuli (Moore, 2013;Rennies, Verhey, & Fastl, 2010;Ries et al, 2008), our results demonstrate that they are not sufficient to predict loudness asymmetries that occur between stimuli of a few seconds. In the view of our data, though it still underestimates the magnitude of the effect, the LTL of Glasberg and Moore's model seems to be the best candidate to evaluate these asymmetries.…”
Section: Predictions From Current Loudness Modelscontrasting
confidence: 83%
“…In these models, the time constants employed at the first integration stage (i.e., to compute the STL) were based only on data from psychophysical experiments on temporal masking and temporal integration of loudness (Glasberg & Moore, 2002). Although some studies showed that these constants surprisingly lead to fairly accurate predictions of loudness asymmetries between short duration rising and falling stimuli (Moore, 2013;Rennies, Verhey, & Fastl, 2010;Ries et al, 2008), our results demonstrate that they are not sufficient to predict loudness asymmetries that occur between stimuli of a few seconds. In the view of our data, though it still underestimates the magnitude of the effect, the LTL of Glasberg and Moore's model seems to be the best candidate to evaluate these asymmetries.…”
Section: Predictions From Current Loudness Modelscontrasting
confidence: 83%
“…It also remains to be shown to what extent models for the loudness of time-varying sounds (e.g., Chalupper & Fastl, 2002;Glasberg & Moore, 2002) can account for some effects of the level profile on the temporal weights. Previous studies have concluded, however, that existing models cannot explain the primacy effect observed with a flat level profile (Pedersen, 2006;Rennies, Verhey, & Fastl, 2010). Note that a recent model of spectral loudness summation predicts an onset accentuation (Rennies, Verhey, Chalupper, & Fastl, 2009), but due to its short effective time constants, the model probably cannot explain the primacy effects observed with sound durations of 1 s, as in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Similar predictions are expected, for instance, from the model for time-varying loudness (Glasberg and Moore, 2002), since the differences between the models are only visible in a very few experiments (Rennies et al, 2010). The present study focused on dynamic loudness models for the simulations since stationary models are not sensitive to amplitude modulations.…”
Section: Modelling Partial Loudness Of a Tone In Noisesupporting
confidence: 76%